FACTORS RELATED TO THE LEATHER CRAFTSMEN’S SELF-SUFFICIENCY IN THE DISTRICTS OF SIDOARDJO AND MAGETAN, EAST JAVA - Hamidah Nayati Utami; Sumardjo . (Jurnal Penyuluhan, 2006)
This research was intended to identify factors related to the leather craftsmen’s self sufficiency in the districts of Sidoarjo and Magetan, in East Java. A descriptive survey research was accomplished amongst 260 craftsmen in the two districts in April 2005 through February 2006. The collected data were analyzed by using the Descriptive Statistics, the One Way Anova and the Structural Equation Modeling procedures. The findings pointed out that most of the observed craftsmen’s entrepreneurial as well as their self-sufficiency behaviors were low. Furthermore, their self-sufficiency behaviors were related to their personal characteristics, business supports, and business environment.